Isothermal annealing of radiation defects in silicon bulk material of diodes from 8” silicon wafers - Kieseler, Jan; Almeida, Pedro Gonçalo Dias de; Kałuzińska, Oliwia Agnieszka; Mühlnikel, Marie Christin; Diehl, Leena; Sicking, Eva; Zehetner, Philipp (Journal of Instrumentation, 2023)
The high luminosity upgrade of the LHC will provide unique physics opportunities, such as the observation of rare processes and precision measurements. However, the accompanying harsh radiation environment will also pose unprecedented challenged to the detector performance and hardware. In this paper, we study the radiation induced damage and its macroscopic isothermal annealing behaviour of the bulk material from new 8” silicon wafers using diode test structures. The sensor properties are determined through measurements of the diode capacitance and leakage current for three thicknesses, two material types, and neutron fluences from 6.5· 1014 to 1 · 1016 neq/cm2.
Gesehen am 01.08.2024